KOMUNIKASI POLITIK ANIES BASWEDAN DALAM MEMBENTUK OPINI PUBLIK MELALUI MEDIA SOSIAL MENJELANG PEMILIHAN PRESIDEN 2024 - Fadhel Azmi Azmi; Boanerges Yoah Amiel; Arale Balqis; Intan Maulida Nabila; Frisca Arindah (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2022)
Political communication is a crucial element that must exist among political actors because political communication can build the image of political actors in the eyes of society. Moreover, the presidential election in Indonesia will take place in about two years. Various issues regarding who will become the candidate pair in the 2024 Presidential Election have been frequently discussed by the media and the public. Various names of political figures are predicted to run for office in 2024. Various responses and public opinion regarding political actors also varied. Some voluntarily supported and some even openly disapproved of the issue of the intended political actor nominating himself in the 2024 presidential election. One example of such a political actor is Anies Baswedan. Anies himself is an example of a political actor who often uses social media to convey his political communications. Social media was chosen because it is the most accessible platform for two-way communication. Therefore, here we will analyze Anies Baswedan's style of political communication on social media and public opinion given by the public.